The Level of Patient Satisfaction with Outpatient Services at the General Poly Primary Health Center of Naikliu, Kupang Regency - Anivista, Sisilia; Regaletha, Tadeus A. L.; Dodo, Dominirsep O. (Universitas Nusa Cendana, 2023)
Patient satisfaction is the result of an assessment of the emotional response that the patient gets because of the fulfillment of expectations for the services received. One form of UKP First Level is outpatient services. The initial survey which was conducted in February 2020, the Head of the Puskesmas gave an overview of the medical services provided by doctors. In 2019, the puskesmas brought in doctors who previously served at the puskesmas near the border, so that in that year the doctors provided services in 2 different work areas. This study aims to determine the level of patient satisfaction with outpatient services, using a quantitative descriptive research method with a cross-sectional study design. Research variables include direct evidence, reliability, responsiveness, assurance, and empathy. The population of this study were all patients who visited the General Polyclinic during the period December 2021-February 2022 totaling 503 visitors with a sample of 83 people and using a simple random sampling technique. The results showed that the level of satisfaction with the category of satisfaction on direct evidence (22.9%), reliability (41%), responsiveness (66.3%), assurance (20.5%), and empathy (36.1%), whereas with the very satisfied category on the dimensions of direct evidence (77.1%), reliability (59%), responsiveness (33.7%), assurance (79.5%), and empathy (63.9%). As a suggestion, it is expected that there will be an evaluation to improve and optimize outpatient services such as adding laboratory personnel, paying attention to the completeness of medical devices and medicines, especially medicines that are often needed by the community.